2003
DOI: 10.4049/jimmunol.170.9.4649
|View full text |Cite
|
Sign up to set email alerts
|

A Role of CXC Chemokine Ligand 12/Stromal Cell-Derived Factor-1/Pre-B Cell Growth Stimulating Factor and Its Receptor CXCR4 in Fetal and Adult T Cell Development in Vivo

Abstract: The functions of a chemokine CXC chemokine ligand (CXCL) 12/stromal cell-derived factor-1/pre-B cell growth stimulating factor and its physiologic receptor CXCR4 in T cell development are controversial. In this study, we have genetically further characterized their roles in fetal and adult T cell development using mutant and chimeric mice. In CXCL12−/− or CXCR4−/− embryos on a C57BL/6 background, accumulation of T cell progenitors in the outer mesenchymal layer of the thymus anlage during initial colonization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
117
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(130 citation statements)
references
References 42 publications
11
117
0
2
Order By: Relevance
“…CXCL12, which is recognized by the CXCR4 receptor, is an essential prerequisite for functional thymocyte migration (33). CXCL12 is produced by both cortical and medullar epithelial cells, and recent studies underline the urgent need for CXCL12/CXCR4 pathway in T lymphocyte development in vivo (34). In single-positive CD4 2 CD8 + or CD4 + CD8 2 T lymphocytes, the expression rate of CXCR4 is reduced, which supports the outflow of naive T lymphocytes into the periphery (35).…”
Section: Discussionmentioning
confidence: 99%
“…CXCL12, which is recognized by the CXCR4 receptor, is an essential prerequisite for functional thymocyte migration (33). CXCL12 is produced by both cortical and medullar epithelial cells, and recent studies underline the urgent need for CXCL12/CXCR4 pathway in T lymphocyte development in vivo (34). In single-positive CD4 2 CD8 + or CD4 + CD8 2 T lymphocytes, the expression rate of CXCR4 is reduced, which supports the outflow of naive T lymphocytes into the periphery (35).…”
Section: Discussionmentioning
confidence: 99%
“…T and B lymphocytes utilize CXCR4 for trafficking and homing to distinct microenvironments within lymphoid tissues and the thymus during development and immune surveillance. 82,132 Another general concern regarding the use of CXCR4 antagonists in cancer patients is the mobilization of normal progenitor cells, such as HSC from their microenvironments to the blood. Mobilized HSCs that are normally protected in marrow niches would be exposed to the effects of cytotoxic drugs in trials where CXCR4 antagonists are administered along with cytotoxic drugs, which could result in prolonged cytopenias.…”
Section: Potential Side Effects Of Cxcr4 Antagonistsmentioning
confidence: 99%
“…Thus, proliferation and differentiation of DN3 cells into DPs on plate-bound DL4 are preTCR dependent. The finding that sorted DN3 cells from Rag-2-deficient mice did not even survive for 3 days in the present culture system further supports this conclusion.It was recently suggested that PI3 kinase signaling mediated by CXCR4 is also involved in the DN3 to DP transition [40][41][42]. To evaluate the contribution of CXCL12 during this differentiation step in the present culture system, we sorted DN3 cells and cultured them in the presence of 10 nM CXCL12.…”
mentioning
confidence: 99%
“…It was recently suggested that PI3 kinase signaling mediated by CXCR4 is also involved in the DN3 to DP transition [40][41][42]. To evaluate the contribution of CXCL12 during this differentiation step in the present culture system, we sorted DN3 cells and cultured them in the presence of 10 nM CXCL12.…”
mentioning
confidence: 99%